2020
DOI: 10.1038/s41529-020-0117-y
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion interactions between stainless steel and lead vanado-iodoapatite nuclear waste form part I

Abstract: This study explores the corrosion interactions between a metallic canister material, stainless steel (SS) 316, and an I-bearing ceramic waste form, lead vanado-iodoapatite (I-APT, Pb 9.85 (VO 4) 6 I 1.7), in a chloride solution. Crevice corrosion of the SS in close proximity to the I-APT resulted in the development of an aggressive environment at the interface of the two materials, which was acidic and enriched in Cl − anions. I-APT also corroded in the crevice region, primarily through ion-exchange between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…However, in a typical SS crevice, the local pH could be lower than 1 12 . This indicates that the crevice corrosion of SS may have been locally suppressed by the corrosion products of I-APT, which is consistent with the results presented in Part I of this paper 25 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, in a typical SS crevice, the local pH could be lower than 1 12 . This indicates that the crevice corrosion of SS may have been locally suppressed by the corrosion products of I-APT, which is consistent with the results presented in Part I of this paper 25 .…”
Section: Discussionsupporting
confidence: 91%
“…7f). The Raman spectra were significantly different compared to those collected from the precipitated phases on SS surface corroded near I-APT (see Part I 25 ). As a matter of fact, the formation of chervetite may be more favorable than apatite under acidic conditions.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Therefore, it is expected that the ion exchange process may be facilitated between the Cl − ions and ceramics with exchangeable anions in a crevice corrosion environment. This hypothesis was validated by Guo, Yao and their colleagues by corroding SS in close proximity to an I-bearing apatite (I-APT) in an oxic environment 91,92 . It was found that the corrosion of I-APT was enhanced by the crevice corrosion of SS, as evidenced by the increased alteration layer thickness in the crevice mouth area of the I-APT.…”
Section: Glass and Steel Corrosion Productsmentioning
confidence: 82%
“…Another interaction mechanism between crystalline ceramics and metals is based on the effects of metal crevice corrosion, as disclosed in recent studies by Guo et al 45,91,92 . who revealed a synergistic corrosion interaction between SS and a Cr-bearing hollandite in an oxic environment 45 .…”
Section: Glass and Steel Corrosion Productsmentioning
confidence: 99%